The Impact of Type 2 Diabetes Mellitus with Corneal Endothelial Cells and Central Corneal Thickness Seen in a Tertiary Care Center in Northwestern Rajasthan - Khyati Yadav; Shilpi Kochar; Devanshi Halwai; Navdeep Kaur; Jaishree Murli Manoher (Delhi Journal of Ophthalmology)
Aims and Objectives: This study investigates the correlation of type 2 diabetes mellitus with corneal endothelial cells and central corneal thickness (CCT). Material and Methods: Using a sample of 311 diabetic and 500 nondiabetic participants, we analyzed endothelial cell density (ECD), cell size variation (CV), hexagonality, and CCT. Results: Diabetic patients exhibited significantly reduced ECD and hexagonality, with increased CV and CCT compared to controls, particularly in cases of long-standing diabetes (≥10 years) and elevated glycated hemoglobin levels (≥7%). Conclusion: The study highlights the need for routine corneal assessments in diabetic care to prevent complications.